Self-awareness and its relationship to the cognitive style (risk - caution) among graduate students - Ammar A. Farhan; Naji A. Rmaied (مجلة جامعة الأنبار للعلوم الإنسانية, 2022)
The aim of the research is to identify the relationship between self-awareness and cognitive style (risk-caution) among a sample of graduate students at the University of Anbar, and to reveal the differences in self-awareness and cognitive style risk-caution according to the gender variable (male - female) and specialization (scientific - human). The study sample consisted of (420) male and female students, and the scale of self-awareness prepared by the researcher was applied to them according to the theory (Bas, 1976). . The researcher also adopted the cognitive style scale (risk - caution), which was prepared by (Abdul-Majid, 2008), and based on the theory of Kagan & Wallach (Kagan & Wallach, 1964), and the scale consisted in its final form on (23) items. After applying the appropriate statistical procedures, the results of the study showed that there is a direct correlation between self-awareness and cognitive style (risk - caution), as postgraduate students at the university use the cognitive method (risk) or graduate students with low self-awareness use the method. Cognitive (caution), and there are no differences in self-awareness among graduate students in the variable of gender and specialization, while it was found that male graduate students are distinguished by the cognitive style (risk) more than female students, and there are no differences in the cognitive style (risk - caution) Among the postgraduate students in the specialization (scientific - human), and in light of the results, the researcher made a number of recommendations and suggestions.